2018
DOI: 10.15324/kjcls.2018.50.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention Effects of Geldanamycin and 17-AAG in Human Oral Squamous Cell Carcinoma

Abstract: Geldanamycin과 17-AAG가 구강편평세포암종 세포주에 미치는 암예방 효과 이은주 대전보건대학교 임상병리과 HSP90 regulates various proteins involved in differentiation and cell survival. Levels of HSP90 tend to increase during development of squamous cell carcinoma in the head and neck including the mouth. Thus, many studies have been conducted to treat these cancers through suppression of HSP90. This study investigated the effect of two HSP90 inhibitors, geldanamycin and 17-AAG, on the proliferation, apoptosis, and invasion of human oral squamous cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Geldanamycin has previously been shown to inhibit muscle regeneration and myogenic differentiation [29,30], and geldanamycin and its derivatives have been previously recognised as anti-cancer agents [51]. In vitro cancer studies in squamous cell carcinoma demonstrated significant inhibition of cell proliferation and G2 arrest by geldanamycin [52], and it inhibited angiogenesis and invasion in a prostate cancer model, mediated by the hypoxiainducible factor 1α [53]. Particularly for mesothelioma, a study by Okamoto et al (2008) showed that in vitro use of tanespimycin, a less-toxic derivative of geldanamycin, led to significant G1 and G2/M cell cycle arrest and apoptosis, while inhibiting cell proliferation in mesothelioma cells [54].…”
Section: Discussionmentioning
confidence: 99%
“…Geldanamycin has previously been shown to inhibit muscle regeneration and myogenic differentiation [29,30], and geldanamycin and its derivatives have been previously recognised as anti-cancer agents [51]. In vitro cancer studies in squamous cell carcinoma demonstrated significant inhibition of cell proliferation and G2 arrest by geldanamycin [52], and it inhibited angiogenesis and invasion in a prostate cancer model, mediated by the hypoxiainducible factor 1α [53]. Particularly for mesothelioma, a study by Okamoto et al (2008) showed that in vitro use of tanespimycin, a less-toxic derivative of geldanamycin, led to significant G1 and G2/M cell cycle arrest and apoptosis, while inhibiting cell proliferation in mesothelioma cells [54].…”
Section: Discussionmentioning
confidence: 99%
“…Geldanamycin has previously been shown to inhibit muscle regeneration and myogenic differentiation (29) (30), and geldanamycin and its derivatives have been previously recognised as anti-cancer agents (49). In vitro cancer studies in squamous cell carcinoma demonstrated significant inhibition of cell proliferation and G2 arrest by geldanamycin (50), and it inhibited angiogenesis and invasion in a prostate cancer model, mediated by the hypoxia-inducible factor 1α (51). Particularly for mesothelioma, a study by Okamoto et al (2008) showed that in vitro use of tanespimycin, a less-toxic derivative of geldanamycin, led to significant G1 and G2/M cell cycle arrest and apoptosis, while inhibiting cell proliferation in mesothelioma cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, variants of geldanamycin have been developed, most notably by altering the quinone ring structure, which have led to improvements in tolerance, potency, metabolic stability, and water solubility (Le Brazidec et al, 2004). Although, the synthesized series of geldanamycin derivatives to make new types of Hsp90 inhibitor with weak toxicity and high efficiency have been attempting (Jurczyszyn et al, 2014;Lee, 2018;Lin et al, 2015;Vasilevskaya et al, 2003). However, there was a limit number of water solubility of these geldanamycin derivatives.…”
Section: Introductionmentioning
confidence: 99%